Metabolic Syndrome as a Risk Factor for Osteoarthritis - Alireza Askari; Zahra Shahabfard; Elham Ehrampoush; Ehsan Bahramali; Reza Homayounfar (Fasa University of Medical Sciences, 2015)
Metabolic syndrome refers to a set of conditions that include high blood pressure, increased insulin level in the blood, the accumulation of the excess fat around the abdomen, and increased blood lipids. In metabolic syndrome, the vast majority of these conditions are simultaneously present, and the risk of developing heart disease, stroke, and diabetes rises. Besides, osteoarthritis or degenerative joint disease is the most common joint disease in humans and is also the main cause of pain and disability in the elderly. The end result of this process is pain and reduced range of motion, and in advanced cases joint inflammation, cartilage destruction, and disability are clinical symptoms of osteoarthritis. Considering the high prevalence of these two disorders in the country and many common pathologic aspects of these two diseases such as obesity and elderly, we decided to review their relationship.